The construction of nature and the nature of construction: incentives for environmental services policies in Acre and Mato Grosso: A construção da natureza e a natureza da construção: políticas de incentivo aos serviços ambientais no Acre e no Mato Grosso - Furtado, Fabrina (Programa de Pós-graduação em Desenvolvimento, Agricultura e Sociedade da Universidade Federal Rural do Rio de Janeiro (CPDA/UFRRJ), 2018)
Alongside the process of deregulation, the loosening and elimination of rights historically achieved through intense processes of struggle and the deepening of the development logicbased on economic and political extractivism, since the beginning of the 2000s, there has been a movement towards the creation of market related environmental regulation regimes associated with the construction of new types and increasingly privatized “natures”. These are laws and logics, which together with the advancement of the agribusiness economy and the deregulation and loosing of rights, promote an intensification of the appropriation of what we understand as nature and consequently explicit processes of violence, exploitation, and expropriation of territories. More specifically it is the idea of nature as an environmental service and related projects, legitimized by the international climate agreements developed since 1992. The material and symbolic appropriation of nature as a solution to the climate crisis and the discursive appropriation of the political and economic crisis that we have experienced since the parliamentary coup of 2016, has led to the creation of new institutions in Brazil based on the market. In order to combat the climate crisis, sub-national institutions and practices such as the Acre's State System of Incentives for Environmental Services (SISA) and the State System for Reducing Emissions from Deforestation and Degradation (REDD+) in Mato Grosso are being created. Based on these two cases, this article seeks to reflect on the political, social, cultural and territorial implications of the creation of market instruments in the context of discourses concerning climate change. It is hypothesized that political problems are often constructed, already containing the means of their solution